KEBERLANJUTAN MATERIAL BAMBU PADA BANGUNAN AULA BAMBU BUMI PEMUDA RAHAYU - Gallus Presiden Dewagana; Kamal A. Arif (Riset Arsitektur (RISA), 2022)
Abstract - The issue of global warming strongly encourages architects to use sustainable materials to preserve nature. Bamboo material is an ecological and sustainable material. Bamboo is also predicted as a future material. The strengths and advantages of bamboo are very likely to be used as a building construction material. Unfortunately, it is not uncommon for bamboo material to be used inappropriately so that it does not optimize the ecological and sustainable properties of bamboo. The object of study chosen was the Bumi Pemuda Rahayu bamboo hall. This object is close to the concept of sustainability as seen from the function of the building, which is a co-creating space that prioritizes sustainability-related activities. This research uses qualitative-quantitative methods that will compare the theory regarding the concept of sustainability of materials related to the building material life cycle with the data obtained. The concept will be divided into three aspects, namely design aspects, construction aspects, and maintenance and renovation aspects. These three aspects can be examined by knowing the object data related to these aspects. The results of the study will answer whether the use of bamboo material in the object of study is in accordance with the concept of sustainability of the bamboo material. The analysis of the design stage pays attention to material selection, material preservation, how to optimize the age of bamboo and the selection of a structural system. The construction stage is analyzed by considering the type of connection used. The maintenance and renovation phases are analyzed by paying attention to how to renovate the bamboo structure and post-construction maintenance of the building. This building is appropriate in choosing the type of material, applying preservation of bamboo materials, and successfully preventing bamboo from environmental influences in order to reach its optimal age. In terms of structural system selection, this building is also appropriate by applying the arc rod structural system. Bolted joints are appropriate for complex structural systems, it's just that there must be special treatment at the base of the arc structure that receives the greatest load due to cracks. Renovation and maintenance aspects must be considered again because this building will have difficulty if you have to do renovations, especially on the arc structure. Maintenance that is rarely performed can also reduce the life of the building. Key Words: bamboo, sustainable materials, Bumi Pemuda Rahayu